On stochastic processes as solutions of a stochastic equation of K. Ito - Surgailis, D. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Д. Сургайлис. О случайных процессах как решениях стохастического уравнения К. ИтоD. Surgailis. Atsitiktiniai procesai kaip stochastinės K. Ito lygties sprendiniai